The Effect of Service Quality and Personal Marketing on Customer Satisfaction and it’s Implications on Syifamart Customer Loyalty (Survey at Syifamart Putri Jalancagak, Subang Regency) - Dian Fitri Damayanti; Kosasih Kosasih; Farida Yuliaty; Ayi Wahid (Dinasti Publisher, 2025)
This study aims to analyze the influence of service quality and personal marketing on customer satisfaction and its implications for customer loyalty at SyifaMart Putri Jalancagak, Subang Regency. The background of this study is based on the increasing competition in the retail business that demands every business actor to be able to provide superior service and build personal relationships with customers. This study used a quantitative method with a survey approach to 105 customers selected through a purposive sampling technique. Data were collected through questionnaires and analyzed using path analysis to test the direct and indirect effects between variables. The results showed that service quality and personal marketing have a positive and significant effect on customer satisfaction, and customer satisfaction has a significant effect on customer loyalty. In addition, customer satisfaction was proven to mediate the effect of service quality and personal marketing on customer loyalty. This study concluded that improving service quality and implementing an effective personal marketing strategy can strengthen SyifaMart's customer satisfaction and loyalty in a sustainable manner.